2015
DOI: 10.1007/s11325-015-1291-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep architecture and obstructive sleep apnea in obese children with and without metabolic syndrome: a case control study

Abstract: Obese children with metabolic syndrome had increased WASO, N1 sleep stage, and severe OSA. But the results regarding sleep architecture are most likely a direct result of OSA severity. More longitudinal studies are needed to confirm the association of metabolic syndrome and OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…This study also found that the frequency of respiratory events, the degree of oxyhemoglobin saturation, and sleep efficiency were all associated with an increased MetS risk. A more recent case–control study of obese children found that OSA was more common in those with vs without the MetS 315. A study of 104 obese children and adolescents, of whom 58% were prepubertal, found an association between oxyhemoglobin desaturation measures and MetS risk 314.…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 99%
“…This study also found that the frequency of respiratory events, the degree of oxyhemoglobin saturation, and sleep efficiency were all associated with an increased MetS risk. A more recent case–control study of obese children found that OSA was more common in those with vs without the MetS 315. A study of 104 obese children and adolescents, of whom 58% were prepubertal, found an association between oxyhemoglobin desaturation measures and MetS risk 314.…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 99%
“…An excess in weight is more crucial for OSA than either age or gender[ 37 , 38 ]. For every percent in weight reduction, there is a 3% reduction in the AHI[ 27 , 39 ].…”
Section: Correlations Between Ms and Osamentioning
confidence: 99%
“…Obesity is a risk factor for both the metabolic syndrome and SDB. Growing evidence suggests that OSAS is a risk factor for the metabolic syndrome in children and adolescents, independent of obesity . A cross‐sectional study of 270 adolescents reported a 6.5‐fold increased risk for the metabolic syndrome among participants with OSAS .…”
Section: Which Co‐existing Conditions May Improve When Treatment For mentioning
confidence: 99%
“…Growing evidence suggests that OSAS is a risk factor for the metabolic syndrome in children and adolescents, independent of obesity. [99][100][101] A crosssectional study of 270 adolescents reported a 6.5-fold increased risk for the metabolic syndrome among participants with OSAS. 102 However, treatment of OSAS by adenotonsillectomy has had variable results on metabolic parameters.…”
Section: Metabolic Syndromementioning
confidence: 99%